Environmental vulnerability of people to brick kiln - K. Saha, M.; Ara, Rowshon; Danish Kadir, S.; G. Mostafa, M. (SPC Journal of Environmental Sciences, 2021)
The study aimed to assess the vulnerability to brick kilns hazards based on questionnaire surveys. It was conducted at 12 selected brick kiln clusters in Rajshahi and Gazipur Districts of Bangladesh. A total number of 700 respondents taking part in the survey from both the study areas. The study identified that most (75%) of the brick kilns were fixed chimney type kilns that impacted crop production, river grabbing, deforestation, solid waste generation, labors right violation, etc. The survey results illustrated that the emission of dust particles, harmful gases, and hot air cause several health hazards such as asthma, eye or skin irritation, etc. The brick kilns have exerted environmental stress on fruit plants such as mango, banana, jackfruit, etc., resulted declining in fruit production. The relationship between the brick kiln owners and community people is not well due to the negative impacts of brick kilns. About 69% of respondents thought that the brick kilns were a vital source of air pollution. Finally, the study concluded that the brick kilns caused threats to society, human health, and the environment around the kiln areas.Â Â